2011
DOI: 10.1051/0004-6361/201014992
|View full text |Cite
|
Sign up to set email alerts
|

Multi-fibre optical spectroscopy of low-mass stars and brown dwarfs in Upper Scorpius

Abstract: Context. Knowledge of the mass function in open clusters constitutes one way to critically examine the formation mechanisms proposed to explain the existence of low-mass stars and brown dwarfs. Aims. The aim of the project is to determine as accurately as possible the shape of the mass function across the stellar/substellar boundary in the young (5 Myr) and nearby (d = 145 pc) Upper Sco association. Methods. We have obtained multi-fibre intermediate-resolution (R ∼ 1100) optical (∼5750−8800 Å) spectroscopy of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
114
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(128 citation statements)
references
References 64 publications
(172 reference statements)
11
114
3
Order By: Relevance
“…These low values agree with the PEWs of Na I doublet measured in other young stars (e.g. Lodieu et al 2011) and are lower than the ≈6 Å typical equivalent widths measured in M old field dwarfs (Martin et al 1996).…”
Section: Luminosity Class and Membershipsupporting
confidence: 89%
See 2 more Smart Citations
“…These low values agree with the PEWs of Na I doublet measured in other young stars (e.g. Lodieu et al 2011) and are lower than the ≈6 Å typical equivalent widths measured in M old field dwarfs (Martin et al 1996).…”
Section: Luminosity Class and Membershipsupporting
confidence: 89%
“…1 and also from the values presented in Table 2 the two spectra are similar, but not identical. A direct comparison of the spectra of CHS 7797 at the two observed phases and spectra of three members of the ≈5 Myr-old Upper Scorpius Association from Lodieu et al (2011) is shown in Fig. 2 2 .…”
Section: Spectral Indices and Spt Determinationmentioning
confidence: 99%
See 1 more Smart Citation
“…The comparison between results based on visible and near-infrared spectroscopy may be affected by such biases, given the greater uncertainties in nearinfrared spectral classifications. However, Lodieu et al (2011) have recently used visible spectroscopy to derive a star-to-brown dwarf ratio of only 2.5 for the Upper Scorpius association, adjacent to the Lupus clouds, based on spectroscopy in the visible. The departure with respect to values found in other regions is mainly due to an overabundance of brown dwarfs with masses below ∼0.04 M that includes a possible secondary peak of the mass function around 0.015 M .…”
Section: Expected New Members and The Mass Functionmentioning
confidence: 99%
“…However, much progress has been made in the last decade with the discovery of ever fainter, less massive members now reaching down to a few Jupiter masses in some nearby star-forming regions (e.g. Luhman 2007;Luhman et al 2009;Spezzi et al 2008;Bihain et al 2009;Boudreault & Bailer-Jones 2009;Scholz et al 2009;Haisch et al 2010;Geers et al 2011;Lodieu et al 2011, for some recent surveys). Much of the progress has come from dedicated surveys using wide-field instruments complemented by A&A 531, A33 (2011) Fig.…”
Section: Introductionmentioning
confidence: 99%